2022
DOI: 10.1093/arclin/acac059
|View full text |Cite
|
Sign up to set email alerts
|

Trail Making Test Could Predict Impairment in Cognitive Domains in Patients with Multiple Sclerosis: A Study of Diagnostic Accuracy

Abstract: Objective Cognitive impairment (CI) and executive dysfunction (ED) are prevalent in patients with multiple sclerosis (PwMS). The Minimal Assessment of Cognitive Function in Multiple Sclerosis (MACFIMS) is the gold standard neuropsychological battery (NPB) for detecting CI. Delis-Kaplan Executive Function System (DKEFS) NPB evaluates ED. We aimed to find practical test(s) from DKEFS with acceptable diagnostic utility for early detection of impairment in cognitive and executive domains. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 50 publications
2
5
0
Order By: Relevance
“…In our study, we found that TMT part A was as easy to use as a screening tool for assessment of information processing speed as SDMT. Previous studies of attention in PwMS found that the TMT test was impaired in RRMS 12,13 . Similar to our results, it was found previously in a cohort study in Indian people that TMT and other cognitive tests were correlated with EDSS and physical disability 14 .…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In our study, we found that TMT part A was as easy to use as a screening tool for assessment of information processing speed as SDMT. Previous studies of attention in PwMS found that the TMT test was impaired in RRMS 12,13 . Similar to our results, it was found previously in a cohort study in Indian people that TMT and other cognitive tests were correlated with EDSS and physical disability 14 .…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies of attention in PwMS found that the TMT test was impaired in RRMS. 12,13 Similar to our results, it was found previously in a cohort study in Indian people that TMT and other cognitive tests were correlated with EDSS and physical disability. 14 Previous studies 15,16 also found that SDMT correlated with EDSS and the number of relapses and can be a predictor of progression and cognitive affection.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…However, while the TMT provides valuable insights into the executive function, relying exclusively on it may overlook other critical facets of this multifaceted construct [ 83 ]. This exclusive reliance on the TMT may yield an incomplete understanding of the executive function, potentially leading to the misinterpretation of cognitive profiles [ 84 , 85 ]. Moreover, the TMT may lack sensitivity in detecting subtle deficits, particularly in individuals with mild cognitive impairment or early-stage neurodegenerative disorders [ 85 ].…”
Section: Discussionmentioning
confidence: 99%